The Association in Myopic Tractional Maculopathy With Myopic Atrophy Maculopathy - Tian, Jiaxin; Qi, Yue; Lin, Caixia; Cao, Kai; Wang, Ningli (Frontiers in Medicine, 2021)
Purpose: To investigate the relationship between myopic tractional maculopathy (MTM) and myopic atrophy maculopathy (MAM). Method: Two hundred and six eyes with definitive myopic retinoschisis were enrolled in the retrospective observational case series study and further evaluated the atrophic and tractional features. Atrophic changes were analyzed according to the atrophic component in the ATN classification and the occurrence of gamma zones and delta zones. Tractional changes were evaluated based on different retinoschisis layers, the location and range of outer retinoschisis, retinal detachment, inner lamellar macular hole (ILMH), outer lamellar MH (OLMH), full-thickness MH (FTMH), and paravascular abnormalities. Results: Of all the eyes, 29.6%, 42.7%, 19.4%, and 8.3% presented MAM grades with A1, A2, A3, and A4, respectively. The three layers of retinoschisis and the entire macular retinoschisis had the highest incidences in A2 (38.6%; 54.5%). The numbers of retinoschisis layers and the grades of outer retinoschisis had a weak negative correlation with MAM (r=-0.138, P=0.048; r=-0.139, P=0.047). All the eyes had gamma zones, and 82.52% of eyes coexisted delta zones. The incidence of retinal detachment and OLMH reached the peak in A2 and then decreased gradually. With MAM aggravation, the prevalence of ILMH decreased. Eyes with A1 and A2 were more likely to have OLMH, and those with A3 and A4 were more likely to have FTMH (P =0.028; OR, 3.423; 95% CI, 1.144-10.236; P =0.004; OR, 7.752; 95% CI, 1.951-30.803). With the MAM grades growing, the types of paravascular abnormalities increased (r=0.165, P=0.018). Conclusion: Diffuse chorioretinal atrophy was the dominant MAM grade in eyes with MTM. In the study, 72.3% of eyes with MTM present diffuse chorioretinal atrophy and tessellated fundus. Beyond 80% of eyes with MTM had both gamma zones and delta zones. Diffuse chorioretinal atrophy might be a complicated stage for MTM with the highest rate of three layers of retinoschisis, the entire macular retinoschisis, RD, and OLMH. The atrophic progression might involve the development of MH. When MTM combines with well-defined atrophy, the occurrence of FTMH should be noted.